Lyme Disease and CNS Complications - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1988)
Four adult patients with chronic meningoencephalitis caused by tick-transmitted Borrelia burgdorferi infection are reported from the Depts of Neurology, University of Freiburg, Freiburg, and University of Koln, Koln, Federal Republic of Germany.